Why serious academic fraud occurs in China. Issue 1 (1st January 2013) - LIN, Songqing
ABSTRACT: While it is clear that academic papers play an important role in the establishment of status in research a misguided academic evaluation system in China leads some researchers to pursue quantity of papers rather than quality, especially Science Citation Index‐indexed papers. It seems some people do anything to get promotion, even to the point of fabricating academic credentials. In recent years some serious academic fraud has been reported in China. The paper is an attempt to discuss the reasons behind such fraud, which, even though it is rare, nevertheless could potentially destroy academic ethics in China.